Römische Erinnerungsräume Heiligenmemoria und kollektive Identitäten im Rom des 3. bis 5. Jahrhunderts n. Chr. - Diefenbach, Steffen (Millennium-Studien / Millennium Studies, 2008)
Between the 3rd and 5th centuries AD Rome underwent a process of transformation which profoundly marked the urban, social, and religious structure of the city. Examing the memory of saints, this study inspects a central field in which this structural change took place. The main themes are, on the one hand, the connection between memoria and various group identities, and, on the other, the specific Christian concept of remembrance, which inturn formed an important prerequisite for the change from a city of late Classical Antiquity to an early medieval city.